Does different social media platforms lead to depression, anxiety, stress and bipolar disorder? a cross-sectional analysis on private University undergraduates - Ting Tin Tin; Lee Kuok Tiung; Ong Jing Hong; Chong Jing Hui; Chew Jia Shen; Tan Yi Jian; Omolayo Michael Ikumapayi (Scopus, 2024)
The widespread use of social media platforms among undergraduate students in Malaysia has raised concerns about its impacts on mental health. Social media expose students to a variety of potential risks, such as cyberbullying and privacy concerns. This study addresses the pressing issue of whether the use of social media influences the mental well-being of undergraduates. The objective is to identify the specific effects of platforms such as YouTube, Facebook, Instagram, and TikTok on student mental health. Using a questionnaire-based convenient sampling methodology, we collected a study sample of 182 students studying at a private university to investigate the correlation between social media use and mental health issues, including stress, anxiety, depression, and bipolar disorder. SPSS is used to conduct Cronbach Alpha for reliability test, and Pearson Correlation for testing the conceptual framework. The results show that Facebook and YouTube significantly affect depression, anxiety, stress and bipolar disorder. TikTok also shows significant impacts on mental health except for stress. Meanwhile, Instagram only significantly affects anxiety. This result is a strong proof that excessive use of social media is correlated with anxiety especially related to physical social life. Facebook, YouTube and TikTok seem to bring more impacts on mental health compared to Instagram. The implication of this study is to provide insights on the factors that influence mental health issues among university students and emphasizes the future need for targeted interventions to mitigate possible harm.